2003
DOI: 10.1034/j.1600-0412.2003.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette, alcohol, and caffeine consumption: risk factors for spontaneous abortion

Abstract: Consumption of 5 or more units alcohol per week and 375 mg or more caffeine per day during pregnancy may increase the risk of spontaneous abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
4
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(105 citation statements)
references
References 26 publications
(43 reference statements)
9
85
4
7
Order By: Relevance
“…Cigarette smoking, alcohol and moderate-to-heavy caffeine and cocaine use58 59 may be associated with sporadic miscarriages; however, the relationship between these factors and recurrent miscarriage is unclear.…”
Section: Aetiology Of and Risk Factors For Recurrent Miscarriagementioning
confidence: 99%
“…Cigarette smoking, alcohol and moderate-to-heavy caffeine and cocaine use58 59 may be associated with sporadic miscarriages; however, the relationship between these factors and recurrent miscarriage is unclear.…”
Section: Aetiology Of and Risk Factors For Recurrent Miscarriagementioning
confidence: 99%
“…However, the literature has yielded inconsistent results regarding the existence of an association. Several studies have found an association between alcohol consumption during pregnancy and miscarriage(Andersen, Andersen, Olsen, Gronbaek, & Strandberg-Larsen, 2012; Armstrong, McDonald, & Sloan, 1992; Chiodo et al, 2012; Harlap & Shiono, 1980; Henriksen et al, 2004; Kesmodel, Wisborg, Olsen, Henriksen, & Secher, 2002; Kline, Shrout, Stein, Susser, & Warburton, 1980; Maconochie, Doyle, Prior, & Simmons, 2007; Rasch, 2003; Windham, Von Behren, Fenster, Schaefer, & Swan, 1997). However, others, including two systematic reviews published in 2006 and 2007, have not(Cavallo, Russo, Zotti, Camerlengo, & Ruggenini, 1995; Henderson, Gray, & Brocklehurst, 2007; Parazzini et al, 1994; Tolstrup et al, 2003; Zhang & Bracken, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating alcohol consumption in continuous or discrete levels of intake have produced more mixed results(Andersen, et al, 2012; Armstrong, et al, 1992; Cavallo, et al, 1995; Chiodo, et al, 2012; Harlap & Shiono, 1980; Henriksen, et al, 2004; Kesmodel, et al, 2002; Kline, et al, 1980; Maconochie, et al, 2007; Parazzini, et al, 1994; Rasch, 2003; Windham, Fenster, & Swan, 1992; Windham, et al, 1997). Most research examining levels of alcohol use has found evidence of a threshold between two to four drinks per week at which alcohol use during pregnancy is related to miscarriage(Andersen, et al, 2012; Armstrong, et al, 1992; Harlap & Shiono, 1980; Henriksen, et al, 2004; Kesmodel, et al, 2002; Kline, et al, 1980; Maconochie, et al, 2007; Rasch, 2003; Windham, et al, 1992; Windham, et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…87,88 Excessive coffee consumption may also increase the risk of miscarriage. 89,90 It seems sensible to strongly recommend a healthy lifestyle and give advice regarding smoking, alcohol and caffeine consumption to couples with recurrent miscarriage.…”
Section: Lifestyle Factorsmentioning
confidence: 99%